Audiology Private Practice: What Students Should Consider - Kassa, Mary (Seminars in Hearing, 2019)
Students who have graduated from a Doctor of Audiology program are qualified to practice as audiologists as determined by university standards, national examination, and state licensure; however, being qualified to practice audiology does not necessarily mean a person is ready to open a private practice. Students may have had a few business or clinic management courses and may have had the opportunity to rotate through private practices; however, these few experiences would not sufficiently prepare them for the realities of owning and operating a business. This article will describe the attributes of an entrepreneur as well as some of the important issues students may wish to consider prior to taking on the responsibility of being the owner of an audiology private practice.
Keywords: doctor of audiology; graduate school; private practice audiology; small business owner; entrepreneur